Pengaruh Fitur Live streaming dan Harga Terhadap Keputusan Pembelian Konsumen Pada Aplikasi E-commerce Shopee di Kabupaten Tangerang The Impact of Live streaming Features and Pricing on Consumer Purchase Decisions on the Shopee E-commerce Application in T - Sholikhah, Fikriyati; Arum, Khorifah; Ekawati, Elfi (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
In this advanced era, technology and information are developing rapidly, including the internet. Currently, many activities are carried out virtually, such as online buying and selling transactions in the Marketplace. Shopee is a specialized application that creates a pleasant online shopping experience for consumers with advanced payment and delivery assistance. The purpose of this study is to obtain information related to various things that can influence young people to make decisions to buy an item about the effect of price and live streaming features on consumer purchasing decisions in the Shopee e-commerce application. This research uses quantitative methods. Sampling was carried out by distributing questionnaires to 100 respondents so that data was obtained to further analyze the effect of the live streaming feature and price on purchasing decisions on the shopee e-commerce application by conducting multiple linear regression analysis. The results of the analysis concluded that the live streaming feature and price, simultaneously (together) have an effect on purchasing decisions on the shopee e-commerce application. While the results of the analysis of the calculation of partial test statistics on the live streaming feature variable have a significant effect on consumer purchasing decisions on the Shopee e-commerce application in Tangerang Regency. Meanwhile, the results of the analysis of the calculation of partial test statistics on the price variable, the price has an individual and significant effect on purchasing decisions in the Shopee e-commerce application in Tangerang Regency.